2013
DOI: 10.3390/cancers5010015
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Impact of HIF-1a on Gastric Cancer Biology

Abstract: Hypoxia inducible factor-1 (HIF-1) monitors the cellular response to the oxygen levels in solid tumors. Under hypoxia conditions, HIF-1α protein is stabilized and forms a heterodimer with the HIF-1β subunit. The HIF-1 complex activates the transcription of numerous target genes in order to adapt the hypoxic environment in human cancer cells. In gastric cancer patients, HIF-1α activation following extended hypoxia strongly correlates with an aggressive tumor phenotype and a poor prognosis. HIF-1α activation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 36 publications
5
83
0
1
Order By: Relevance
“…In GC, previous studies have also reported that HIF-1α activation following extended hypoxia strongly correlates with an aggressive tumor phenotype and poor prognosis of patients (16)(17)(18)(19). Therefore HIF-1α is recognized as a central regulator of GC pathogenesis (14,20). Reactive oxygen species (ROS) such as superoxide are generated mainly through the electron transport chain (ETC) (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In GC, previous studies have also reported that HIF-1α activation following extended hypoxia strongly correlates with an aggressive tumor phenotype and poor prognosis of patients (16)(17)(18)(19). Therefore HIF-1α is recognized as a central regulator of GC pathogenesis (14,20). Reactive oxygen species (ROS) such as superoxide are generated mainly through the electron transport chain (ETC) (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Under normoxia, prolyl hydroxylases (PHDs) hydroxylate proline residues of HIF-1α in a reaction that uses O 2 as a substrate, and the modified HIF-1α is subsequently degraded by the ubiquitin proteasome system. Under hypoxia, HIF-1α protein is stabilized owing to the absence of O 2 substrate and instead forms a heterodimer with the HIF-1β subunit (11)(12)(13)(14). The HIF-1 complex then activates the transcription of hundreds of target genes and leads to adaptation to the hypoxic environment (11,12 has been reported to upregulate target genes related to energy metabolism, angiogenesis, cell proliferation or survival, invasion or metastasis, and drug resistance in human cancer cells (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia inducible factor-2 subunit α (HIF-2α) is a key factor in angiogenesis, tumor growth and endothelial growth during the remodeling process of tumorigenesis (8 (9). VEGFA is part of the VEGF structural family of proteins, and is among the most potent angiogenic factors expressed in different types of human cancer, including HCC, breast cancer, clear cell renal carcinoma and gastric cancer (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Ki67, HIF, E cadherin, MMP-1, TGF-B, STAT3, TIMP1, HER2 in gastric cancer but amongst all, p53 was studied considerably [10][11][12][13][14] . The immunohistochemical protein expression of p53 has been proposed as a potential tool to evaluate the behavior biologically.…”
Section: Introductionmentioning
confidence: 99%